FENOMENA INDEKS PEMBANGUNAN GENDER (IPG) DAN INDEKS PEMBERDAYAAN GENDER (IDG) DALAM MENINGKATKAN PARTISIPASI ANGKATAN KERJA WANITA DI INDONESIA - Sari, Dewi Puspita; Nailufar, Fanny; Anwar, Khairil; Rahmah, Mutia (Jurnal Ekonomi Regional Unimal, 2024)
This study aims to determine the effect of the Gender Development Index (GDI) and Gender Empowerment Index (GEI) on the female labor force participation rate in Indonesia. This research uses Secondary data sourced from Badan Pusat Statistik (BPS) Indonesia for the period 2008-2022. The data was analyzed using Multiple Linear Regression analysis method. Partial research results show that the Gender Development Index (GDI) variable has no effect and is not significant to the Female Labor Force Participation Rate and the Gender Empowerment Index (GEI) variable has an effect and is significant to the Female Labor Force Participation Rate in Indonesia. Simultaneously, the Gender Development Index (GDI) and Gender Empowerment Index (GEI)variables have a significant effect on the Female Labor Force Participation Rate in Indonesia.